Tensile behavior in selective laser melting - Ortiz Rios, Cesar; Amine, Tarak; Newkirk, Joseph W. (International journal of advanced manufacturing technology, 2018)
By the nature of selective laser melting (SLM) additive manufacturing (AM), property variations are likely to arise in specific structures of parts. The problem here is that it is hard to predict exactly how properties will be affected or conversely, how the mechanical properties in local sections of the built parts can be intentionally changed. There is little known about how build geometry and grain structures unique to SLM affects the mechanical properties of SLM parts. To address this issue, various SLM manufactured parts, created using the Renishaw ™ AM 250, were tested for significant variation in mechanical properties. Specifically, the use of both mini tensile tests and Automated Ball Indentation (ABI) is employed to incrementally test localized sections. ABI has the potential to greatly improve the ability to monitor properties. This research advances collective understanding of AM and leads to methods that assure property uniformity or intentional manipulation of mechanical properties.